An Exploratory Study of Long-Term Outcome Measures in Critical Illness Survivors: Construct Validity of Physical Activity, Frailty, and Health-Related Quality of Life Measures*. Issue 6 (June 2016) - McNelly, Angela S.; Rawal, Jai; Shrikrishna, Dinesh; Hopkinson, Nicholas S.; Moxham, John; Harridge, Stephen D.; Hart, Nicholas; Montgomery, Hugh E.; Puthucheary, Zudin A.
Abstract : Objective: Functional capacity is commonly impaired after critical illness. We sought to clarify the relationship between objective measures of physical activity, self-reported measures of health-related quality of life, and clinician reported global functioning capacity (frailty) in such patients, as well as the impact of prior chronic disease status on these functional outcomes. Design: Prospective outcome study of critical illness survivors. Setting: Community-based follow-up. Patients: Participants of the Musculoskeletal Ultrasound Study in Critical Care: Longitudinal Evaluation Study (NCT01106300), invasively ventilated for more than 48 hours and on the ICU greater than 7 days. Interventions: None. Measurements and Main Results: Physical activity levels (health-related quality of life [36-item short-form health survey] and daily step counts [accelerometry]) were compared to norm-based or healthy control scores, respectively. Controls for frailty (Clinical Frailty Score) were non-morbid, age- and gender-matched to survivors. Ninety-one patients were recruited on ICU admission: 41 were contacted for post-discharge assessment, and data were collected from 30 (14 female; mean age, 55.3 yr [95% CI, 48.3–62.3]; mean post-discharge, 576 d [95% CI, 539–614]). Patients' mean daily step count (5, 803; 95% CI, 4, 792–6, 813) was lower than that in controls (11, 735; 95% CI, 10, 928–12, 542; p < 0.001), and lower in those with preexisting chronic disease than without (2, 989 [95% CI, 776–5, 201] vs 7, 737 [95% CI, 4, 907–10, 567]; p = 0.013). Physical activity measures (accelerometry, health-related quality of life, and frailty) demonstrated good construct validity across all three tools. Step variability (from SD) was highly correlated with daily steps ( r 2 = 0.67; p < 0.01) demonstrating a potential boundary constraint. Conclusions: Subjective and objective measures of physical activity are all informative in ICU survivors. They are all reduced 18 months post-discharge in ICU survivors, and worse in those with pre-admission chronic disease states. Investigating interventions to improve functional capacity in ICU survivors will require stratification based on the presence of premorbidity. Abstract : Supplemental Digital Content is available in the text.